Leading Apple with Steve Jobs : management lessons from a controversial genius - Elliot, Jay. (Hoboken, N.J.: Wiley, 2012)
Jay Elliot, former Senior VP of Apple, shares how Steve Jobs motivated people to do the best work of their lives. Elliot was hired by Steve Jobs, just in time to accompany him on his last historic visit to Xerox's Palo Alto Research Center. Jay Elliot served as Steve's right-hand man and trouble-shooter, overseeing all corporate operations and business planning, as well as software development and human relations. In this book, he details how Steve managed and motivated his people. Steve Jobs used phrase "Pirates! Not the Navy" as a rallying cry, a metaphor to "Think Different." In developing the Macintosh, it became a four-word mission statement. Management principles that grew out of that statement form backbone of this book: How to find talented people who will understand your objectives and be able to make a contribution to that effort ; Lists traits that can determine whether a person will be so committed to the vision that they will provide their own motivation ; How to ensure that employees hold an allegiance to the captain and to his/her shipmates, and also possess the ability to come up with original, unique ways to approach a problem, and be self-guided with a strong sense of direction.
Preface : Why I wrote this book -- A ding in the universe : everything starts with an inspiring vision -- Steve's business philosophy and values -- People who know more than you : choosing and leading your lieutenants -- Steve's secrets for selecting great people -- Unusual interviewing techniques -- To protect innovation, create a company within a company -- "No more crap products" : creating excellence -- More on product strategy : design is how it works -- Entrepreneurial confidence and high standards -- Employee owners : rewarding the product stakeholders -- The Apple workplace : fostering creativity -- When selling becomes more important than the product -- "And one more thing" : looking into the distance -- Flowers at his doorstep : the heritage of Steve Jobs.
Includes bibliographical references and index.
Keywords: Jobs, Steve, -- 1955-2011.; Jobs, Steven, -- 1955-2011; Jobs, Steve, -- 1955-2011; Apple Computer, Inc; Apple Computer Inc; Apple Computer, Inc -- -- Management; Computer industr -- United States; Führungsgrundsatz; Computerindustrie; Unternehmen; Management; Industrial management; Computer industry; Industrial management; United States; USA